Principles of microwave measurements - Bryant, G. H. (Geoff H.) (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1993)
The book covers the fundamental theoretical bases of modern microwave measurements in the time and frequency domains, including reflectometry, spectrum analysers, vector and scalar analysers, multiports, power, noise, frequency stability and time domain reflectometry. It offers a comprehensive account of far-and-nearfield antennas measurements.
Electronic reproduction.
Keywords: Microwave measurements; Microwaves; Electronic books